Faktor-Faktor yang Mempengaruhi Produksi Kakao (Theobroma cacao L.) Di Kecamatan Padang Gelugur Kabupaten Pasaman - Angelia Leovita (Mediagro: Jurnal Ilmu-ilmu Pertanian, 2025)
The largest cocoa producer is Pasaman Regency, one of which is Padang GelugurDistrict. The main challenge in the sustainability of the cocoa business is thatproduction has not reached its maximum potential. This study aims to 1) Describethe characteristics of cocoa farmers in Padang Gelugur District, Pasaman Regency2) Analyze the factors that influence cocoa production in Padang Gelugur District,Pasaman Regency. This study uses qualitative descriptive analysis methods andquantitative analysis using Cobb-Douglass production function analysisThe resultsshow that 1) Farmers 1) Cocoa farmers in Padang Gelugur District are dominatedby men aged 37 to 40 years with a high school education level, the number of familydependents is 4 to 5 people. Farming experience of 10 to 12 years, monthly incomebetween Rp. 2,900,000 to Rp. 3,583,000. 2) The variables of chemical fertilizer(X1), pesticide (X2), plant age (X3), land area (X4), TKDK (X5), pruning (D1)Control of plant pests and diseases (D2) have a significant effect on cocoaproduction, while TKLK (X6) does not have a significant effect on cocoaproduction.and non-family labor (X8).